Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1097/00006842-198609000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Diminished pulse pressure under mental stress characterizes normotensive adolescents with parental high blood pressure.

Abstract: An exaggerated blood pressure response to mental stress is believed to characterize young adults with genetic risk of essential hypertension, suggesting that stress-induced changes might provide a useful index of pathogenetic processes. We explored this by studying pressor responsivity to competitive tasks in adolescents drawn from a large urban population. Individuals with systolic or diastolic pressures persistently between the 85th and 95th percentiles were evaluated on basal blood pressure, parental histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The SCI in- creased systolic and diastolic pressures by approximately 13 mm Hg, as compared with approximate 8 mm Hg increases during the cognitive tasks. The latter changes were nearly identical with the mean 9 mm Hg/6 mm Hg video game blood pressure increases we obtained previously in research on a very similar adolescent sample (15). The SCI raised subjects' heart rates but changes were less dramatic than the blood pressure responses.…”
Section: Subject Characteristicssupporting
confidence: 87%
“…The SCI in- creased systolic and diastolic pressures by approximately 13 mm Hg, as compared with approximate 8 mm Hg increases during the cognitive tasks. The latter changes were nearly identical with the mean 9 mm Hg/6 mm Hg video game blood pressure increases we obtained previously in research on a very similar adolescent sample (15). The SCI raised subjects' heart rates but changes were less dramatic than the blood pressure responses.…”
Section: Subject Characteristicssupporting
confidence: 87%
“…Adolescents with parental high BP were characterized by a comparatively higher DBP and lower SBP, resulting in a chronically reduced pulse pressure. These adolescents’ SBP increased less under mental stress (video game task) than did SBP of adolescents with normotensive parents, suggesting an underreactive cardiac output (Ewart et al, 1986). At present it is not clear if this reduced pulse pressure reflects a distinctive pathogenetic mechanism in the parental risk adolescents or if it merely indicates an earlier progression of disease.…”
Section: Discussionmentioning
confidence: 93%
“…An important question confronting such an effort arises from a finding we have reported in a previous article (Ewart, Harris, Zeger, & Russell, 1986). Adolescent participants at increased risk of adult hypertension due to having a BP persistingly greater than P85 and also a history of high BP or heart disease in a biological parent had a distinctive cardiovascular pattern that separated them from participants with BP greater than P85 and no familial risk.…”
Section: Discussionmentioning
confidence: 99%
“…Over half the case/control comparisons failed to detect increased reactivity in higher risk offspring, and risk group differences were weaker and less consistent in individuals under the age of 20 than in adults. A striking example of this inconsistency was provided by our own earlier biracial study of normotensive adolescents with blood pressures between the 85th and 95th percentiles relative to children of the same age and sex (3). In this normal but higher risk group, offspring of hypertensive parents did not demonstrate greater blood pressure reactivity to a video game task than did offspring of normotensive parents; on the contrary, comparison of the two offspring groups showed that those with parental hypertension were characterized by a diminished pulse pressure response to the stressor.…”
Section: Introductionmentioning
confidence: 99%